PERKEMBANGAN FISIK PADA MASA ANAK-ANAK AWAL - Innayah, Azzira; Azzahra, Nazwa; Khoiri, Muhammad Lutfi; Lubis, Ihsan Rinaldi (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2023)
Physical development in early childhood is a critical period that forms an important foundation for health and well-being throughout life. This research focuses on using library research methods to present a comprehensive literature review related to physical development in this valuable phase. The results highlight the crucial role of genetic, nutritional, and environmental factors in shaping children's growth. This review explores the influence of social environment, cognitive stimulus, and positive interpersonal interactions in shaping motor development and social skills in early childhood. The implications of this research may provide a basis for the design of more effective health and education interventions to ensure optimal physical development in children at this valuable phase.